Architecture for an efficient MBIST using modified March-y algorithms to achieve optimized communication delay and computational speed. Issue 1 (18th January 2021) - O.S., Nisha; K., Sivasankar
Abstract : Purpose: In this work, an efficient architecture for memory built in self-test (MBIST) that incorporates a modified March Y algorithm using concurrent technique and a modified linear feedback shift register (LFSR)–based address generator is proposed. Design/methodology/approach: Built in self-test (BIST) is emerging as the essential ingredient of the system on chip. In the ongoing high speed, high tech sophistication technology of the very large-scale integrated circuits, testing of these memories is a very tedious and challenging job, since the area overhead, the testing time and the cost of the test play an important role. Findings: With the efficient service of the adapted architecture, switching activity is considerably cut down. As the switching activity is in direct proportion to the power consumed scaling down, the switching process of the address generator inevitably leads to the reduction in power consumption of the MBIST. Originality/value: To improve the yield and fault tolerance of on-chip memories without degradation on its performance self-repair mechanisms can be implemented on chip.